Broad-Spectrum Supramolecularly Reloadable Antimicrobial Coatings - Artusio, Fiora; Müller, Lukas; Razza, Nicolò; Cordeiro Filipe, Inês; Olgiati, Francesca; Richter, Łukasz; Civera, Edoardo; Özkan, Melis; Gasbarri, Matteo; Rinaldi, Louisa; Wang, Heyun; Garcìa, Esther; et al. (ACS Applied Materials and Interfaces, 2024)
Antimicrobial surfaces limit the spread of infectious diseases. To date, there is no antimicrobial coating that has widespread use because of short-lived and limited spectrum efficacy, poor resistance to organic material, and/or cost. Here, we present a paint based on waterborne latex particles that is supramolecularly associated with quaternary ammonium compounds (QACs). The optimal supramolecular pairing was first determined by immobilizing selected ions on self-assembled monolayers exposing different groups. The QAC surface loading density was then increased by using polymer brushes. These concepts were adopted to develop inexpensive paints to be applied on many different surfaces. The paint could be employed for healthcare and food production applications. Its slow release of QAC allows for long-lasting antimicrobial action, even in the presence of organic material. Its efficacy lasts for more than 90 washes, and importantly, once lost, it can readily be restored by spraying an aqueous solution of the QAC. We mainly tested cetyltrimethylammonium as QAC as it is already used in consumer care products. Our antimicrobial paint is broad spectrum as it showed excellent antimicrobial efficiency against four bacteria and four viruses.
CRIS-Team Scopus Importer:2024-06-14
Keywords: antimicrobial surfaces; quaternary ammonium compounds; reloading; scalability; supramolecular interactions